Comparison between the Effectiveness of Manual Acupuncture and Laser Acupuncture at EX-B3 Weiwanxiashu in a Rat Model of Type 2 Diabetes - Ahmad Aulia Jusuf; Yoshua Viventius; Wahyuningsih Djaali (Medical Association of Pharmacopuncture Institute, 2021)
Background : Diabetes mellitus (DM) is a chronic metabolic disease characterized by increased blood sugar levels. The current management of DM to date has a target of controlling blood glucose, but the therapy cannot be separated from long-term drug side effects. Acupuncture can be an option as an adjunct therapy for DM. Objectives: The purpose of this study was to compare the effectiveness between manual acupuncture and laser acupuncture. Methods : This study was a randomized control experimental study with a pretest and posttest design using 24 male Sprague-Dawley rats divided into 4 groups: a normal group, a diabetes group, an acupuncture group, and a laser group. Manual acupuncture and laser acupuncture were performed 6 times in two weeks. Fasting blood glucose (FBG) levels, the cell density of Langerhans islets, and side effects were assessed and compared among the 4 groups. Results : The highest mean cell density of Langerhans islets was found in the laser and acupuncture group, and the lowest was found in the diabetes group. In the post hoc analysis, the normal, acupuncture, and the laser groups had a significantly higher mean cell density than the diabetes group. The lowest mean FBG level was in the laser group, followed by the acupuncture group, and the highest was in the diabetes group, but this difference was not significant. There were no serious side effects from the use of manual acupuncture or laser acupuncture. Conclusion : Both manual acupuncture and laser acupuncture can improve the histological findings of Langerhans islets in type 2 diabetic rats, and both are safe to use.